Centrality and get-richer mechanisms in interregional knowledge networks. Issue 11 (2nd November 2018) - Mitze, Timo; Strotebeck, Falk
ABSTRACT: This study analyzes the determinants of a region's centrality position in research collaboration networks and their variation over time. Focusing on the German biotechnology industry, we use data on collaboration activities among NUTS-3 regions in 2005 and 2009 to construct centrality measures and relate them to sector-region-specific and overall regional attributes in an explorative regression approach. The results indicate that fit-get-richer mechanisms proxied by regional endowments and policy factors such as biotech research and development funding categories and human capital matter for network formation. We find that these correlations differ across centrality measures and that empirical evidence for a richer-get-richer mechanism is limited.